The prevalence, associations and symptoms of depression amongst dementia sufferers. - Ballard, C; Bannister, C; Solis, M; Oyebode, F; Wilcock, G (1996)
OBJECTIVE: To examine the prevalence rates of RDC major and RDC minor depression in dementia sufferers, to compare the prevalence rates and symptoms of depression between different dementias and to look at the associations of RDC major depression. DESIGN: Case control. SETTING: Referrals to clinical services. SUBJECTS: 124 patients with DSM-III-R dementia. MEASURES: The patients were assessed using the GMS/HAS package and the Cornell Depression Scale. Depression was diagnosed according to RDC criteria. RESULTS: 25.0% of patients had RDC major depression and 27.4% had RDC minor depression. Major depression occurred significantly more often and was significantly more severe in patients with vascular dementia than patients with Alzheimer's disease. Severe visual impairment was significantly associated with RDC major depression in Alzheimer's disease and physical health problems were significantly associated with depression in vascular dementia. Most symptoms of depression including suicidal thoughts were common. CONCLUSIONS: Major depression is more common and more severe in patients with vascular dementia. The associations of depression may be different in these patients.